(untitled) (Journal of Asian Development Studies, 2022)
The study has explored the impact of cash transfers on women empowerment in Pakistan. Women empowerment is basically providing women power in space of society where they not have, this promote to gender equality and help to attain sustainable developmental goals (SDG’S) 2030. To measure the women empowerment an index generated with five factor of women decision making (marriage decision, children decision, and food purchasing decision, cloth purchasing decision and travel decision) through Principle Component Analysis (PCA). Data extracted from Household Integrated Economic Survey (HIES) 2018-19 in Pakistan. Cash transfers used as a combination of Benazir Income Support Program (BISP), Zakat/Usher and other sources. Geography (rural or urban) of household, Information and Communication Technology (ICT) proxy of usage of mobile, desktop, laptop or other device and Head of Household (male or female) used as control variables. According to data nature Ordinary Least Square (OLS) regression applied in this research. After checking the impact of cash transfers on women empowerment in Pakistan, impact of disaggregated cash transfer also examined. Outcomes of this research shows that cash transfers have positive impact on women empowerment in Pakistan, head of household has negative impact on women empowerment, its mean if female will be head of household it will positively contribute in women empowerment, but if men will be head than its impact will be negative on women empowerment. Information and communication technology and geography have positive impact on women empowerment. Disaggregated results indicates that Benazir Income Support Program has positive but negligible influence on women empowerment, Zakat/Usher has great role in women empowerment, while other sources not have any vital role in women empowerment.